2021
DOI: 10.1177/0957926521992150
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of critical discourse analysis and its implications

Abstract: As critical discourse analysis/studies move into the second decade of the 21st century, there is a need to reflect on their evolution and envision their future development. In this paper, CiteSpace and VOSviewer are employed to gain holistic insights into CDA/CDS research and capture the recent research foci. The Web of Science core collection database is a prominent resource for collecting data. It was found that (1) CDA has broadly absorbed the theories of other disciplines and increasingly developed into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The keywords in the articles can indicate the fundamental aspects of the study field (Xiao & Li, 2021). Thus, emerging trends in research can be identified by analyzing the co-occurrence of keywords, and “the profile of a specific field can be examined via keyword cluster analysis” (Xiao & Li, 2021, p. 493). The keywords cluster analysis was adopted to highlight emerging trends in register studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The keywords in the articles can indicate the fundamental aspects of the study field (Xiao & Li, 2021). Thus, emerging trends in research can be identified by analyzing the co-occurrence of keywords, and “the profile of a specific field can be examined via keyword cluster analysis” (Xiao & Li, 2021, p. 493). The keywords cluster analysis was adopted to highlight emerging trends in register studies.…”
Section: Resultsmentioning
confidence: 99%
“…As the visual analytic approach of the network, the advantage of CiteSpace and VOSviewer-based bibliometric analysis can be utilized to comprehensively insight into the research structure and grasp the current research focus based on statistical quantitative profiling and reliable databases (Xiao & Li, 2021, p. 485). For instance, Xiao and Li (2021) employed CiteSpace and VOSviewer-based methods to explore critical discourse analysis’s research status and implications. Figure 1 is the research steps of bibliometric analysis of register studies.…”
Section: Methodsmentioning
confidence: 99%
“…Keyword visualization map analysis can only grasp the evolutionary context of knowledge association and is inadequate to capture the vagaries of an academic field, because they do not account for the impact of the timeliness of various publications (Xiao and Li, 2021). For this reason, we conduct clusters analyses of keywords to highlight emerging research directions and cutting-edge in terms of CDA in news discourse (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, bibliometric analyses of discourse research have emerged in major discourse analysis journals such as Discourse and Society and Discourse and Communication (Huan and Guan, 2020 ; Xiao and Li, 2021 ). Casting a wider net in the field of critical discourse analysis, Xiao and Li ( 2021 ) conducted a bibliometric and co-citation study of critical discourse studies that were published in the Web of Science (WoS) database between 2011 and 2020 to unravel research trends. In the retrieved 8,137 studies, they discovered information about the scope of research, collaboration between countries and institutions, most prolific authors, and emerging research trends.…”
Section: Introductionmentioning
confidence: 99%